2021
DOI: 10.9734/ejnfs/2021/v13i1130465
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Composition and Health Benefits of Underutilized Green Leafy Vegetables in Ghana: A Review

Richard Osafo

Abstract: Diverse indigenous leaf and fruit vegetables are rich sources of nutrients that cater for the populace especially for those residing in rural areas. However, inadequate knowledge of their constituents and health benefits have decreased its consumption in recent years as opposed to exotic vegetables. Hence to promote their consumption, nutritional, phytochemical, ethnomedicinal and pharmacological properties of the four most popular and widely used indigenous vegetables in several parts of Ghana; Corchorus olit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…TLVs are a very inexpensive resource for tackling undernutrition and malnutrition which are prevalent in Ghana. There is, therefore, a need to create awareness that will encourage their consumption in a bid to reduce malnutrition and attain the UN Sustainable Development Goal of achieving food security, improving nutrition, and promoting good health and well-being by 2030 (Osafo, 2021). Recent studies have shown that traditional leafy vegetables contain non-nutrient bioactive phytochemicals that have been linked to protection against cardiovascular and other degenerative diseases (Kwenin, Wolli, & BM, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…TLVs are a very inexpensive resource for tackling undernutrition and malnutrition which are prevalent in Ghana. There is, therefore, a need to create awareness that will encourage their consumption in a bid to reduce malnutrition and attain the UN Sustainable Development Goal of achieving food security, improving nutrition, and promoting good health and well-being by 2030 (Osafo, 2021). Recent studies have shown that traditional leafy vegetables contain non-nutrient bioactive phytochemicals that have been linked to protection against cardiovascular and other degenerative diseases (Kwenin, Wolli, & BM, 2011).…”
Section: Introductionmentioning
confidence: 99%